2013
DOI: 10.1182/blood-2013-04-497545
|View full text |Cite
|
Sign up to set email alerts
|

Risk profile and clinical outcome of symptomatic subsegmental acute pulmonary embolism

Abstract: Key Points Patients with subsegmental PE appear to mimic those with more proximally located PE regarding their VTE risk profile and clinical outcome. Patients with subsegmental PE significantly differ from patients without PE in terms of both VTE risk profile and clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
6
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 22 publications
8
95
6
4
Order By: Relevance
“…Also, when compared with patients without PE, patients with subsegmental PE were at an increased risk of VTE during follow-up (hazard ratio, 3.8; 95% CI, 1.3-11.1). The study indicates that in contrast to the common belief that subsegmental PE represents a benign subset of VTE, patients with symptomatic subsegmental PE have comparable prognosis as patients with segmental or more proximal PE regarding short-term clinical course (34). Thus, subsegmental PE is clinically relevant and should be reported when present.…”
Section: Ct Diagnosis Of Subsegmental Pementioning
confidence: 58%
“…Also, when compared with patients without PE, patients with subsegmental PE were at an increased risk of VTE during follow-up (hazard ratio, 3.8; 95% CI, 1.3-11.1). The study indicates that in contrast to the common belief that subsegmental PE represents a benign subset of VTE, patients with symptomatic subsegmental PE have comparable prognosis as patients with segmental or more proximal PE regarding short-term clinical course (34). Thus, subsegmental PE is clinically relevant and should be reported when present.…”
Section: Ct Diagnosis Of Subsegmental Pementioning
confidence: 58%
“…Clinical data have suggested that treating patients with these presentations with anticoagulants may not be necessary in the absence of cardiopulmonary compromise, concurrent DVT or persistent risk factors for recurrent VTE [68,69]. However, a recent analysis of 3728 patients with clinically suspected PE found a similar prevalence of VTE risk factors and 3-month risk of recurrent VTE and mortality in patients with subsegmental PE as in those with more proximal PE [70], suggesting that these presentations should be taken seriously, at least when symptoms or other factors are present. These patients could be candidates for outpatient treatment, particularly now that direct OAC treatment is an option.…”
Section: Inpatient Versus Outpatient Management Of Pementioning
confidence: 94%
“…В одном из последних ретроспективных исследований 2 когорт больных с подозрением на ТЭЛА при субсегментар ной и более проксимальной ТЭЛА получены одина ковые результаты (частота рецидивов в течение 3 мес. и летальность), которые во многом зависли от сопутствующей патологии [205]. Определение суб сегментарной ТЭЛА не стандартизовано, и одиноч ный субсегментарный дефект визуализации, скорее всего, не имеет такого же клинического значения, как множественные субсегментарные тромбы.…”
Section: нерешенные вопросыunclassified